IMPROVING ABILITY TO READ THE QUR'AN USING THE YANBU'A METHOD IN MI MUHAMMADIYAH ACADEMIC YEAR 2022/2023 - Ihsan, Muh Nur; Subando, Joko (Proceeding of International Conference of Islamic Education, 2023)
This study aims 1) to find out how the effect of tajwid lessons on students' Al-Quran reading ability, 2). To find out how the influence of the Yanbu'a method on students' ability to read the Koran, 3). To find out how the Impact of Tajweed Lessons and the Yanbu'a Method on the Ability to Read the Al-Quran MI Muhammadiyah Nogosari Boyolali Students for the 2022/2023 Academic Year. This research is a type of classroom action research. This research was conducted from March to May 2023. The subjects of this study were students of MI Muhammaiyah Nogosari Boyolali with a population of 27 students, so all were taken. Data is taken through documents and questionnaire scores, with the T-Test test. The Yanbu'a method can instill the ability to read hijaiyah letters by 22% starting from pre-action, then continuing in cycle I to increase to 70.4% and in cycle II to increase again to 96.3%. The planting of the Yanbu'a method which is applied at MI Muhammadiyah Corner with a classical, individual and reading-oriented system is oriented towards Yanbu'a beginners' books and Yanbu'a volume 1 which is still elementary level children so that students can more easily and quickly accept reading, learn hijaiyah letters.